Rising Powers and Peacebuilding : Breaking the Mold? - Call, Charles T; de Coning, Cedric; Call, Charles T; de Coning, Cedric (Basingstoke Springer Nature, 2017)
peacebuilding; multilateralism; diplomacy; United Nations
English
Keywords: International relations; peacebuilding; multilateralism; diplomacy; United Nations